(untitled) (Journal of Medical & Health Sciences Review, 2025)
Balanced nutritional diet is extremely important for every individual from infancy to throughout adulthood life, to be physically fit and able to execute daily tasks in best possible way. Every nutrient has specific function in a body for different aspects of life. Infant body needs are different from other age group individuals. For the early 6 months the nutritional requirements are being fulfilled by mother milk, but after 6 months infants’ need more balance and nutritional diet to maintain healthy growth. After infancy when infant enter into other stage of his or her life which is childhood their nutritional requirements increase for healthy growth and development. During childhood their requirements are different and enhanced which need to be fulfilled for brain and all other body parts healthy development. To protect children from malnutrition all the body requirements need to be fulfilled by parents from nutrients that are present in food. Nutritionist play important role in balancing this need of children by guiding their parents. This study was conducted to evaluate the perspective of the parents about the need of the nutritionist for their infants. It should help policy makers and health department to formulate their plans in order to make sure the healthy development of the new generation. The study was conducted through survey, the data was collected through interview schedule to collect result-oriented data. The study was conducted in Faisalabad district where two major public sector hospitals were selected for data collection, seventy-five interviews from each hospital were conducted to formulate equal data sheet.